Efektivitas Pemberian Pakan Grindal Worm (Enchytraeus Buchholzi) dan Cacing Sutra (Tubifex SP) Terhadap Pertumbuhan Ikan Sidat (Anguilla SPP) - Suryaman Suryaman; Arif Supendi; Novita MZ; Dasep Hasbullah; Adi Gumbara (Lembaga Pengembangan Kinerja Dosen, 2026)
This study evaluated the effectiveness of Grindal Worm (Enchytraeus buchholzi) and Bloodworm (Tubifex sp.) as live feeds on the growth performance of eel (Anguilla spp.) during the glass eel stage. As a high-value aquaculture commodity with increasing global demand, eel production requires effective feeding strategies to enhance growth and survival during early development. A quantitative descriptive method with an experimental approach was applied. A total of 5,862 glass eels were reared in six aquariums, each containing 977 individuals. Two feeding treatments were tested: Grindal Worm and Bloodworm. Growth performance was assessed based on weight gain, length increment, and survival rate (SR), while data were analyzed using an independent sample t-test. The results demonstrated that glass eels fed with Grindal Worm achieved significantly higher weight gain and length growth than those fed with Bloodworm. Survival rates were also slightly higher in the Grindal Worm treatment. Water quality remained within optimal ranges throughout the experiment, with pH values of 7.6–8.16, dissolved oxygen of 4.9–6.3 mg/L, and temperatures of 21.4–23.3°C, ensuring suitable environmental conditions. Statistical analysis indicated a significant effect of feed type on growth performance (p < 0.05). Therefore, Grindal Worm is recommended as a more effective live feed than Bloodworm for improving the growth and survival of glass eels in aquaculture.